Optimizing electrocaloric effect of PbSc0.5Ta0.5O3 ceramics near/below room temperature by ordering degree modulation - Ruowei Yin; Yuxuan Hou; Xiaowei Lv; Junjie Li; Rongju Zhong; Yanjing Su; Lijie Qiao; Renchao Che; Lifeng Zhu; Chuanbao Liu; Yang Bai (Journal of Advanced Ceramics)
Lead scandium tantalate (PbSc0.5Ta0.5O3 (PST)) is one of the most promising ferroelectric materials for electrocaloric (EC) refrigeration because of its large enthalpy change (ΔH) at room temperature (RT), whose properties are determined by the ordering arrangement of two kinds of heterovalent ions at B-sites. This work continuously adjusts the ordering degree (Ω) for PST ceramics on a large scale from 0.51 to 1 via multiple heat treatment processes. For the PST sample with Ω = 1, large ΔH = 1.06 J/g and very large EC adiabatic temperature change ΔTmax = 4.26 K@60 kV/cm are obtained because of the highly ordered arrangement of the Sc3+ and Ta5+ ions. With decreasing Ω, the Curie temperature (TC) gradually shifts from RT to below 0 °C, and the phase transition is diffused. A fairly large ΔTmax = 1.57 K is obtained at a rather low temperature of 0 °C in the ceramic with Ω = 0.51. This work proves that lattice ordering is another efficient route to modify ferroelectric features, and the achieved large ΔTmax in a wide temperature range near/below RT facilitates high-performance cooling devices with a cascade design toward the most urgent market needs.